From the first equation,
x+5 = 3(y+5)
x = 3y + 15 - 5
Now substitue x in the second equation with (3y +15 - 5).
x-5 = 7(y-5)
(3y+15-5) - 5 = 7(y-5)
3y +5 = 7y - 35
-4y = - 40
y = 10
Since y is 10, and x is (3y +15 - 5),
x = 30 + 15 - 5 = 40
Step-by-step explanation:
they are similar by AA .
<em><u>plz </u></em><em><u>mark</u></em><em><u> my</u></em><em><u> answer</u></em><em><u> as</u></em><em><u> brainlist</u></em><em><u> plzzzz</u></em><em><u> </u></em><em><u>.</u></em><em><u> </u></em><em><u>hope</u></em><em><u> this</u></em><em><u> will</u></em><em><u> be</u></em><em><u> helpful</u></em><em><u> to</u></em><em><u> you</u></em><em><u>.</u></em>
Answer: equation of the tangent plane is z = 1
Step-by-step explanation:
Given equation
z = e^(-x²-y²) at point (0,0,1)
now let z = f(x,y)
Δf(x,y) = [ fx, fy ]
= (-2xe^(-x²-y²)), (-2ye^(-x²-y²))
now
Δf (0,0) = [ 0, 0 ] = [ a, b ]
equation of the tangent plane therefore will be
z - z₀ = a(x-x₀) + b(y-y₀)
z - 1 = 0(x-0) + 0(y-0)
z - 1 = 0 + 0
z = 1
Therefore equation of the tangent plane is z = 1
Answer:
60 mph
Step-by-step explanation:
mph=miles/hours
240/4=60
60 miles per hour